Camostat mesilate, a serine protease inhibitor, exerts aquaretic effects and decreases urinary exosomal AQP2 levels - Yutaka Kakizoe; Terumasa Nakagawa; Yasunobu Iwata; Qinyuan Deng; Masataka Adachi; Yoshikazu Miyasato; Miyuki Nakagawa; Yu Nagayoshi; Kayo Nishiguchi; Yuki Narita; Yuichiro Izumi; Takashige Kuwabara; et al. (Elsevier, 2022)
Serine proteases (SPs) play physiological roles in the kidney. We previously reported that a synthetic SP inhibitor, camostat mesilate (CM), suppressed sodium reabsorption in the renal tubule and showed natriuretic effects in aldosterone-infused rats. Here, we aimed to explore novel physiological roles of SPs in the renal tubule and understand the mechanism of actions of SP inhibitors, by administering CM to healthy rats. Sprague-Dawley rats were classified into control and CM (subcutaneous sustained-release pellet) groups and sacrificed on day 7. CM significantly increased urine volumes by approximately two-fold in a urinary sodium- and osmolyte excretion-independent manner, indicating the occurrence of free water excretion. Serum vasopressin, potassium, and calcium levels and the osmolality in the renal medulla, which all affect free water reabsorption in the renal tubule, remained unchanged after CM administration. CM decreased urinary exosomal AQP2 excretion, suggesting suppression of AQP2 activity in the collecting duct. These changes were reversed by desmopressin infusion. Water diuresis caused by CM was independent of its action on prostasin or TMPRSS4. Our results revealed the association of SP inhibition with free water handling and demonstrated that CM administration exerted diuretic effects with AQP2 downregulation, suggesting SP inhibitors as a new class of aquaretic drugs.